Las divisorias de aguas como elementos del paisaje - González Hidalgo, José Carlos (Geographicalia, 2017)
Given that the drainage network analysis in some circunstances is not eficient to know the patterns of runoff (areas with low rainfall), in this work is presented a divide line study having in mind that the divide lines are the places from where the overland flow begin.